Mechanisms of inmune response in insects - URIBE-SOTO, SANDRA (Revista Colombiana de Entomología, 1997)
Understanding the immune responses of insects is necessary because they are economically important as agricultural pests and disease vectors. Although much information about insect immunity is available from research entomologists, poor knowledge about it is common among most entomologists students and workers. The aim of this review was to collect and present information obtained from the published works concerning this topic and to generate interest for understanding the immune responses and its practica] implications for the control of pests and parasites transmitted by insects.